Analysis Of The Quality Of Education Services For Teachers Of Al-Ikhlas Tsanawiyah Madrasayah Tanjung Sakti Pumi Lahat Regency - Yeni Novita Sari; Marko Ilpiyanto; Darmin Darmin (Journal of Law, Social Science, and Management Review, 2026)
The title of this research is "Analysis of the Quality of Educational Services at Al-Ikhlas Tanjung Sakti Pumi Junior High School, Lahat Regency." The purpose of this study is to determine and analyze the quality of educational services at Al-Ikhlas Tanjung Sakti Pumi Junior High School, to identify and analyze the factors influencing the improvement of educational service quality at Al-Ikhlas Tanjung Sakti Pumi Junior High School, and to identify and analyze strategies for improving the quality of educational services at Al-Ikhlas Tanjung Sakti Pumi Junior High School. The data analysis techniques used were data analysis, data reduction, data presentation, data verification, and data analysis techniques. The results showed that tangible indicators, reliability indicators, and assurance indicators were all functioning well but needed further optimization. The inhibiting factors in improving the quality of teachers at Madrasah Tsanawiyah Al-Ikhlas Tanjung Sakti Pumi from the research results are: discipline, there are still teachers who are less disciplined in obeying school regulations and there is still a lack of existing learning media such as projectors which are only 2. Meanwhile, supporting factors include: discipline, there are still teachers who are less disciplined in obeying school regulations and there is still a lack of existing learning media such as projectors which are only 2. While supporting factors include: the use of learning resources outside the classroom that can be utilized such as: nature, and the environment as well as the existence of good interaction and communication between school residents and parents. While the principal's strategy in implementing the improvement of the quality of MTS Al-Ikhlas Tanjung Sakti Pumi teachers is by involving teachers in scientific forums (seminars, training, workshops, workshops and courses), further studies, welfare allowances, provision of supporting facilities such as provision of internet facilities to access new information, purchasing new books that support teacher performance and involving teachers in professional certificate programs